Aplikasi Online Marketplace pada PT.XYZ di Surabaya - Hermawan Heriyanto; Adi Wibowo; Alexander Setiawan (Jurnal Infra, 2016)
Security is to be expected in the transaction process of buying and selling online. This can be realized by the joint account system. One example is the implementation of a joint account marketplace. In Indonesia there are various kinds of marketplaces such as www.lazada.com, bukalapak.com and www.tokopedia.com.Based on this background PT. XYZ trying to make an application online marketplace which is supported by the joint account system. This application is expected to create security and comfort in the process of buying and selling. The entire transaction process, complaint or advertisement will be integrated in the system, thereby reducing the risk of human error.Overall the application in accordance with the needs of the company and the community. Feel the ease and security of society in the process of purchasing goods without fear of fraud. So also with suppliers will find it easy to get a customer.